Kaempferol improves glucose uptake in skeletal muscle via an AMPK-dependent mechanism - William T. Moore; Jing Luo; Dongmin Liu (Food Science and Human Wellness)
Insulin resistance is a hallmark of type-2 diabetes (T2D) pathogenesis. Because skeletal muscle (SkM) is the major tissue for insulin-mediated glucose disposal, insulin resistance in SkM is considered a major risk factor for developing T2D. Thus, the identification of compounds that enhance the ability of SkM to take up glucose is a promising strategy for preventing T2D. Our previous work showed that kaempferol, a flavonol present in many foods, improves insulin sensitivity in obese mice, however, the mechanism underlying this beneficial action remains unclear. Here, we show that kaempferol directly stimulates glucose uptake and prevents lipotoxicity-impaired glucose uptake in primary human SkM. Kaempferol stimulates Akt phosphorylation in a time-dependent manner in human SkM cells. The effect of kaempferol on glucose uptake was blunted by inhibition of glucose transporter 4, phosphoinositide 3-kinase (PI3K), or AMPK. In addition, kaempferol induced AMPK phosphorylation, and inhibition of AMPK prevented kaempferol-stimulated Akt phosphorylation. In vivo, kaempferol administration induced rapid glucose disposal accompanied with increased Akt and AMPK phosphorylation in SkM tissue of the mice. Taken together, these findings suggest that kaempferol stimulates glucose uptake in SkM via an AMPK/Akt dependent mechanism, and it may be a viable therapeutic agent for insulin resistance.